DESCRIPTION OF DENTAL CARIES ON PANORAMIC RADIOGRAPH AT RSGM UNJANI CIMAHI INDONESIA - Rina Putri Noer Fadilah; Mutiara Sukma Suntana; Khaulah Maryam Jamiilah (Journal of Health and Dental Sciences, 2023)
Panoramic radiograph was a diagnostic method that can see the overall picture of caries in the maxilla and mandible, with a wide range of caries lesions. The large detail area seen on the panoramic radiograph was instrumental for diagnosing caries location for the entire jaw. This study aimed to determine the appearance of dental caries based on panoramic radiographs at RSGM Unjani. This research was a descriptive study using probability techniques in the form of simple random sampling with 43 panoramic radiographs as a sample. The results of the study showed that in panoramic radiographs at RSGM Unjani that the highest frequency based on sex was female patients, the highest frequency based on age were patients in the 45-65 years age group, the highest frequency was based on the incidence location of dental caries were patients with dental caries in the anterior teeth and M1 teeth, and the frequency of caries in deciduous teeth was 100% in the 5-11 years age group. The study conclusion was all panoramic radiographs at RSGM Unjani have caries. DOI : 10.54052/jhds.v3n1.p43-52